EFFECTIVENESS OF HYDROCOLLOID USE ON WOUND HEALING PROCESS IN WOUND PATIENTS AT HANIFAH MEDIKA CENTER PRIMARY CLINIC - Naziyah Naziyah; Maryati Maryati; Rizki Hidayat (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Wounds due to tissue damage can be caused by pressure, friction, extreme temperatures, or infection. WHO from 2022 recorded a wound prevalence of 3.50 per 1000 population, with the majority of cases resulting from surgery or trauma (48%). In Indonesia, around 35% of the population experiences wounds, with pressure ulcers reaching 20%. Nurses play a crucial role in wound care, including the selection of appropriate dressings. Hydrocolloid is a modern dressing that protects wounds from water, air, and bacteria, and creates a moist environment to accelerate healing. This study evaluates the effectiveness of Hydrocolloid in accelerating the wound healing process at the Hanifah Medika Center Primary Clinic. Aim to examine the effect of using the hydrocolloid on wound healing process in wound patient at Hanifah Medica Center clinic. Methods This study was a quantitative design with the Quasi-Experiment methode without a Control Group Pre-Test - Post-Test. In this design, the intervention is given to one group without a control group for comparison. Results: The results showed that mean of pre-test Winner scale score of 28.23 ± 3.093 and a post-test score of 15.63 ± 3.090. The research results indicate a difference in the Winner scale assessment scores between the pre-test and post-test, with a P-value of 0.000 (p-<0.05). Conclusion There was a decrease in wound assessment scores using the Winner scale, with a pre-test score of 28.23 ± 3.093 and a post-test score of 15.63 ± 3.090. which means that the use of Hydrocolloid is effective in the wound healing process. Suggestion: It is suggested that nurses, healthcare institutions, and wound patients can use Hydrocolloid as a dressing continuously. The three of them become one of the efforts in the wound healing process.